2023
DOI: 10.12982/nlsc.2023.037
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Activity of the Hypothalamic-Pituitary-Adrenal Axis after Acute Aerobic Exercise in Obese Women

Abstract: The increase of cortisol hormone and blood pressure indicates the active Hypothalamic-Pituitary-Adrenal axis (HPA-axis) and Sympathetic-Adreno-Medullary-axis (SAM-axis). Someone with obesity tends to have a more active HPA-axis and SAM-axis. Exercise is proclaimed as an effective model to reduce the HPA-axis and SAM-axis activities. This study aims to describe the HPA-axis and SAM-axis activities on the moderate-intensity aerobic. The participants of this study were 20 obese female teenagers aged 20 to 24 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The study yielded a reduction in cortisol levels following a single moderate-intensity exercise session (Figures 1 and 2). These results align with research conducted by Sugiharto et al (2023), who reported that acute or single sessions of moderate-intensity exercise reduced serum cortisol levels in obese women. Previous studies have also reported that moderate-intensity acute exercise reduces cortisol response (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study yielded a reduction in cortisol levels following a single moderate-intensity exercise session (Figures 1 and 2). These results align with research conducted by Sugiharto et al (2023), who reported that acute or single sessions of moderate-intensity exercise reduced serum cortisol levels in obese women. Previous studies have also reported that moderate-intensity acute exercise reduces cortisol response (Wang et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Obesity is a condition that can affect metabolic health, which is characterized by abnormal hormone levels in the body (Velasco-Orjuela et al, 2018). One of them is characterized by increased levels of the hormone cortisol in individuals with obesity (Sugiharto et al, 2023;Hewagalamulage et al, 2016). An alternative to dealing with obesity is exercise.…”
Section: Introductionmentioning
confidence: 99%